2020
DOI: 10.3389/fmech.2020.00033
|View full text |Cite
|
Sign up to set email alerts
|

Review on the Bubble Dynamics Based Cavitation Dynamics for the Negative Squeeze Motion in Lubricated Contacts

Abstract: Simulation models for the cavitation dynamics in lubricated contacts can be roughly clustered into two groups: either without or with bubble dynamics, the first one being the standard case for most fluid film bearing calculations. The approach with bubble dynamics has been introduced to the lubrication community about 20 years ago by Someya, and it is based on the coupling of Reynolds equation and Rayleigh-Plesset equation. It has been used for journal bearings, squeeze film dampers, and it is essentially requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…1) It is difficult to consider the discontinuity film height conditions, but they can also be found in practice, such as for pocket bearings [4,6] and the textured journal bearings [25]. Due to the non-differentiable nature at the discontinuity points, we cannot employ the PINNs method to obtain the solutions directly.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) It is difficult to consider the discontinuity film height conditions, but they can also be found in practice, such as for pocket bearings [4,6] and the textured journal bearings [25]. Due to the non-differentiable nature at the discontinuity points, we cannot employ the PINNs method to obtain the solutions directly.…”
Section: Limitationsmentioning
confidence: 99%
“…For the cavitation research there are still some open questions, such as the effects of the micro-jet and the shockwave caused by the cavitation on the pitting [1]. In this work we focus on the cavitation in lubrication, and extensive papers on this topic for both numerical and experimental ways can be found, and the reader is referred to the reviews of Dowson et al [2], Braun et al [3], Geike [4], and Kamat et al [5] For analyzing the lubrication problems, the Reynolds equation has been widely used, but the effects of cavitation are not considered in it. In order to analyze the film pressure behaviors with the cavitation effects, attempts have been made by many researchers and different cavitation models have been developed [6].…”
Section: Introductionmentioning
confidence: 99%
“…An overview of research results on the simulation of cavitation dynamics can be found in the publications [2,3]. There is one common feature of all simulations known to the author: they do not reproduce the fine spatial structures as observed in experiments.…”
Section: Tensile Stresses Are Reproduced In Simulation Models With Bubble Dynamicsmentioning
confidence: 99%
“…The original model of the author yielded qualitatively reasonable results, but three key issues remained [3].…”
Section: Introductionmentioning
confidence: 96%